Analysis of the economic efficiency of the development of the mining industry of the Republic of Kazakhstan - Nabiyev Е.Н.; Shakeyev С.С.; Nevmatulina K.А. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
The mining industry of Kazakhstan is the most important basic element of the national economy,it plays a decisive role in the national economy and is the supplier of most of the mineral raw materials and fuel. The extractive industry is recognized as one of the priorities that determine the economic potential of the country as a whole, its export opportunities. The extractive industry occupies the main place in solving the problems of economic development of the country. At the moment, the growth rate of the mining industry is characterized by a slight decrease due to a sharp deterioration in the global market situation and economic conditions in general. In this regard, the authors analyzed the main indicators characterizing the current state of the extractive industry in Kazakhstan, which will determine the place and role of this sector in the development of industry and the country’s economy as a whole, as well as determine the degree of influence of the level of its development.